Evaluation of passively induced shoulder stretch reflex using an isokinetic dynamometer in male overhead athletes - Heinke, L. N.; Knicker, A. J.; Albracht, K. (Isokinetics and Exercise Science, 2018)
BACKGROUND: Muscle stretch reflexes are widely considered to beneficially influence joint stability and power generation in the lower limbs. While in the upper limbs and especially in the muscles surrounding the shoulder joint such evidence is lacking. OBJECTIVE: To quantify the electromyographical response in the muscles crossing the shoulder of specifically trained overhead athletes to an anterior perturbation force. METHODS: Twenty healthy male participants performed six sets of different external shoulder rotation stretches on an isokinetic dynamometer over a range of amplitudes and muscle pre-activation moment levels. All stretches were applied with a dynamometer acceleration of 10,000 ° /s 2 and a velocity of 150 ° /s. Electromyographical response was measured via sEMG. RESULTS: Consistent reflexes were not observed in all experimental conditions. The reflex latencies revealed a significant muscle main effect (F (2,228) = 99.31, p < 0.001; 2 = 0.466; f = 0.934) and a pre-activation main effect (F (1,228) = 142.21, p < 0.001; 2 = 0.384; f = 1.418). The stretch reflex amplitude yielded a significant pre-activation main effect (F (1,222) = 470.373, p < 0.001; 2 = 0.679; f = 1.454). CONCLUSION: Short latency muscle reflexes showed a tendency to an anterior to posterior muscle recruitment whereby the main internal rotator muscles of the shoulder revealed the most consistent results.